On Differential Subordinations of Multivalent Functions Involving a Certain Fractional Derivative Operator - Jae Ho Choi (International Journal of Mathematics and Mathematical Sciences)
We investigate several results concerning the differential subordination of analytic and multivalent functions which is defined by using a certain fractional derivative operator. Some special cases are also considered.